Can the side effects of sanctions and energy inflation trigger the disintegration of the international monetary regime? - Roberto Lampa; Gianmarco Oro (PSL Quarterly Review, 2023)
This article aims to discuss the impact of the energy crisis exacerbated by the Russo-Ukrainian war on the general macroeconomic performance and income distribution of the Eurozone. We consider the restrictive monetary policies induced by the return of inflation, their declared and implicit objectives, and the contradictory consequences for the economic system. We analyse the impact of Western sanctions on the Russian economy, and discuss the long-term consequences of sanctions and political strategies on the de-dollarisation of global markets.
Keywords: F51; E32; F44; 330; euro crisis; inflationary processes; post-war economic development